Parasites of the Lionfish Complex (Pterois volitans and P. miles) in the Western North Atlantic, Gulf of Mexico, and Caribbean Sea: Evidence of the Enemy Release Hypothesis? - Simmons, Kayelyn Regina; Kerstetter, David W.; Blanar, C. (NSUWorks, 2014)
The establishment of the invasive lionfish complex Pterois volitans and P. miles from the Indo- Pacific into the Western Atlantic, Gulf of Mexico, and the Caribbean Sea has had significant negative effects on reef fish biodiversity in these areas. The rapid colonization and high abundance of lionfishes in their expanded range have been attributed to several aspects of their biology and life history, such as a varied diet and high fecundity. Invasive lionfishes may also be benefiting from enemy release, experiencing decreased predation and / or parasitism pressure relative to native fishes. However, the parasite fauna of invasive lionfishes remain poorly studied; making it difficult to assess the potential role parasite release may have played in their successful invasion of the Greater Caribbean. To address this knowledge gap, endoparasite biodiversity and community structure were assessed in 516 lionfishes from 15 sites in the Western North Atlantic, Gulf of Mexico, and Caribbean Sea. Sites ranged from Bermuda and North Carolina southwards to Trinidad and Tobago, effectively covering much of the hosts’ expanded range. The most commonly observed parasite was the digenean Lecithochirum floridense. Eight new parasites were described for the first time in lionfishes: a cymothoid isopod, Rocinela stignata; four nematodes, Raphidascaris sp., Contracaecum sp., Paracuaria adunca and Hysterothylaceum sp.; one digenean: Tergestia sp.; two acanthocephalans, Serracentis sp. and Dollfusentis sp., and two cestodes: Nybelinia sp. and Tentacularia sp. A leech, tentatively identified as Trachelobdella lubrica, was also noted. Regarding parasite community structure, several patterns emerged. First, the endoparasite fauna of invasive Lionfishes was largely composed of widely-occurring generalist species. Second, endoparasite diversity and abundance were low (1-6 species); we did not observe any parasites in lionfishes from Bonaire, Barbados, or Texas. Thus, our data suggest that lionfishes may be benefiting to some extent from release from parasitism. Third, although there were broad differences among sites in endoparasite community structure, none could be correlated to broad ecological factors such as latitude, although there were slight differences among bioregions (ANOSIM Global-R0.069, p = 0.014). Lastly, lionfishes from the east coast of Florida exhibited the highest endoparasite abundances and diversity in this survey. We regressed endoparasite species diversity against date of first observation of lionfishes at each site, and found a significant (r2 = 0.368 ,DF = 1, F = 7.57, p = 0.017) positive relationship. Previous studies have noted increasing parasite diversity and abundance in introduced species in the years following their establishment; we suggest that a similar process may be at work in Greater Caribbean lionfishes.